PENGARUH IKLIM ORGANISASI, KOMPETENSI DAN MOTIVASI TERHADAP KINERJA PEGAWAI DI KANTOR PERDAGANGAN INDUSTRI DAN LINGKUNGAN HIDUP DI TIMOR LESTE - Jesus, Luis de; Supartha, Wayan Gede (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.08.NO.01.TAHUN 2019, 2018)
Performance society together often shows no maximum for several reasons such as the lack of qualified human resources, organizational climate which is less in control, inadequate employee competence and motivation of employees who have never been in perioritaskan, it can negatively impact the performance of employees in the organization. This study aimed to assess the effect of organizational climate, employee competence, employee motive, against knerja Employee Work, On Industry and Commerce office environment in East Timor. Samples are 119 clerks. Data was collected through questionnaires later on though with SPSS and analyzed using multiple linear regression analysis. Analysis results prove that the Organizational Climate positive and significant effect on the performance of employees, as well as Proven competence and significant positive effect, and the motive proved positive and significant impact on employee performance. Validation of the model shows Iklm organization, competence and motivation positive and significant impact on employee performance (Y). From the analysis it can be seen that the regression coefficient organizations Iklm variable (X1), has a positive and significant impact on employee performance (Y). Competence (X2), has a positive and significant impact on employee performance (Y). motivation (X3), has a positive and significant impact on employee performance (Y). Results of the analysis concludes that climate variables organization, competence and motivation positive and significant impact on performance. But keep in perioritaskan above is, Climate Organization and the motive of work, because the results of the analysis showed both these variables still need to be improved and in order to fix the future performance of the work in these offices will be improved to achieve organizational goals better than the previously.